Determinan Profitabilitas Dengan Ukuran Perusahaan Sebagai Variabel Moderasi Pada Bank Umum Syariah - Aida Maudi; Amrizal Amrizal; Rizky Maulana Pribadi; Silvi Reni Cusyana (Jurnal Akuntansi dan Governance, 2020)
This research is to empirically examine the effect of corporate social responsibility (CSR), good corporate governance (GCG), and zakat on profitability with company size being a moderating variable. The sample was selected utilizing a purposive sampling technique using 35 samples obtained from the Sharia Commercial Bank financial statements for the 2012-2018 periods. These results prove that CSR and zakat also have a significant effect on profitability, besides CSR cannot affect profitability. Company size can moderate the relationship between CSR and GCG with profitability, While the size of the company weakens the relationship of zakat with profitability.